2005
DOI: 10.1007/s11892-005-0005-4
|View full text |Cite
|
Sign up to set email alerts
|

Glucokinase, glucose homeostasis, and diabetes mellitus

Abstract: The enzyme glucokinase (GK) regulates the rate of glucose metabolism in many tissues, including liver, the pancreatic b cells, certain neurons, enteroendocrine cells, and the pituitary, serving as a glucose sensor in many of these. Thus, GK plays a critical role in glucose homeostasis. Spontaneous mutants of GK in humans result in autosomal-dominant hypo- and hyperglycemia syndromes described as "GK disease." GK activator drugs have been discovered that lower blood glucose in normal and diabetic animals and pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
82
0
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(85 citation statements)
references
References 39 publications
2
82
0
1
Order By: Relevance
“…InserN161 is the second reported MODY2 mutation resulting in the insertion of one extra amino acid in GCK. Previous work revealed that the insertion of an alanine residue at position 454 in the allosteric activator site of GCK activated the enzyme [6]. The novel mutation found in family P33 resulted in the insertion of an asparagine residue between aspartic acid 160 and lysine 161, in the β7 strand, located in the middle of the small domain of GCK (Fig.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…InserN161 is the second reported MODY2 mutation resulting in the insertion of one extra amino acid in GCK. Previous work revealed that the insertion of an alanine residue at position 454 in the allosteric activator site of GCK activated the enzyme [6]. The novel mutation found in family P33 resulted in the insertion of an asparagine residue between aspartic acid 160 and lysine 161, in the β7 strand, located in the middle of the small domain of GCK (Fig.…”
Section: Discussionmentioning
confidence: 92%
“…GCK plays a role as a beta cell glucose sensor by integrating blood glucose levels and glucose metabolism with insulin secretion [4][5][6]. This specific function of GCK is based on the particular kinetic characteristics of this enzyme, which include a low affinity for glucose, cooperativity with this substrate, and a lack of end-product inhibition at physiological concentrations.…”
Section: Introductionmentioning
confidence: 99%
“…GCK also participates in regulating glycogen synthesis and gluconeogenesis in the liver (1). GCK activity is allosterically controlled in hepatocytes by the glucokinase regulatory protein (GCKR), which reversibly binds to GCK and inhibits its activity in the presence of fructose 6-phosphate.…”
mentioning
confidence: 99%
“…Adenoviral-mediated hepatic overexpression of GCKR in mice with high-fat diet-induced diabetes improves fasting and glucoseinduced glycemia and leads to a concomitant increase in insulin sensitivity and triglyceride levels and a decrease in leptin levels (5). Heterozygous mutations in GCK resulting in a reduction of enzymatic activity are responsible for a subtype of monogenic diabetes (maturity-onset diabetes of the young-2) (1,6). Previous genetic studies at the GCKR locus have not reported intragenic mutations associated with type 2 diabetes in humans (7,8).…”
mentioning
confidence: 99%
“…In the pancreatic ␤-cells, GCK controls insulin secretion and biosynthesis (1). In the liver, GCK regulates glycogen synthesis and gluconeogenesis, and its activity is competitively inhibited by glucokinase regulatory protein (GCKR) (1,2).…”
mentioning
confidence: 99%